Evaluation of Proteus vulgarisfimbriae antigen by delayed type hypersensitivity (DTH)-skin test in rabbits - Al-Samarrae, Ekram Abbas Abood (The Iraqi Journal of Veterinary Medicine, 2011)
The aim of this study is to evaluate the use of fimbriae antigens for immunization of rabbits against Proteus vulgaris bacteria results showed a higher significant difference (P<0.05) in erythema diameters in the immunized groups in compared with the control. There was no significant difference between both immunized groups 200 μg/ml and 100 μg/ml after 24 hours. Also, a higher significant differences (P<0.05) in the diameter of induration is recorded in both immunized groups compared to control site, a higher significant differences (P<0.05) in the immunized group (100 μg/ml) at the concentration 200 μg/ml compared with 100 and 50 μg/ml after 24 hours, as follow as after 48 hours except significant differences between 200 and 100 μg/ml concentration (P<0.01) and increase induration after 72 hours between both immunized groups; within groups and control site. Conclusion that the fimbrial antigen have the ability to elicit cellular immune response by delayed type hypersensitivity (DTH).